Controllable synthesis of cross-linked CoAl-LDH/NiCo2S4 sheets for high performance asymmetric supercapacitors. Issue 16 (November 2017) - Zhang, Xiao; Wang, Senlin; Xu, Lin; He, Taobin; Lu, Fengxia; Li, Huichang; Ye, Junhui
Abstract: Cross-linked CoAl-LDH/NiCo2 S4 sheets hybrids hold a promising electrochemical material for high-performance supercapacitors. In this paper, we report a simple strategy for fabricating flocculent NiCo2 S4 decorated on CoAl-LDH nanosheets to form integrated hybrid architectures (CoAl-LDH/NiCo2 S4 ) via hydrothermal and electrodeposition method. Benefiting from the integrated structures of CoAl-LDH/NiCo2 S4 sheets, which can provide a short diffusion path for electrolyte ions and a high utilization rate for electrode materials, the resultant CoAl-LDH/NiCo2 S4 hybrid electrode exhibits a high specific capacity of 1.52 C cm −2 （760 C g −1 ）at the current density of 2 mA cm −2, a superior rate capability of 78.94% when the current density is increased to 10 mA cm −2, much higher than the simple CoAl-LDH nanosheets electrode. An asymmetric supercapacitor fabricated using the cross-linked CoAl-LDH/NiCo2 S4 hybrids as the positive electrode and 3D reduced graphene oxide (rGO) aerogel as negative electrode shows a high energy density of 44.67 W h kg −1 at a power density of 0.4 kW kg −1, and an energy density of 24.4 W h kg −1 can be retained even at a high power density of 4.0 kW kg −1 .